2021
DOI: 10.1038/s41598-021-88164-0
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles using plant Lawsonia inermis and their mosquitocidal, antimicrobial, anticancer applications showing moderate side effects

Abstract: Microbes or parasites spread vector-borne diseases by mosquitoes without being affected themselves. Insecticides used in vector control produce a substantial problem for human health. This study synthesized zinc oxide nanoparticles (ZnO NPs) using Lawsonia inermis L. and were characterized by UV–vis, FT-IR, SEM with EDX, and XRD analysis. Green synthesized ZnO NPs were highly toxic against Anopheles stephensi, whose lethal concentrations values ranged from 5.494 ppm (I instar), 6.801 ppm (II instar), 9.336 ppm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 52 publications
(44 reference statements)
1
13
0
1
Order By: Relevance
“…These absorption peaks are attributed to charge transfer from valence band to conduction band in ZnO. The absorption peak of capped ZnO NPs showed a blue shift due to the decrease in particle size [45].…”
Section: Characterization Of Zno Npsmentioning
confidence: 99%
“…These absorption peaks are attributed to charge transfer from valence band to conduction band in ZnO. The absorption peak of capped ZnO NPs showed a blue shift due to the decrease in particle size [45].…”
Section: Characterization Of Zno Npsmentioning
confidence: 99%
“…On the other hand, Selim et al [ 12 ] also observed remarkable anticancer activity of ZnO-NPs of aqueous extract of Deverra tortuosa on human lung adenocarcinoma (A549) cells. According to Rasmussen et al [ 69 ], the possible mechanism of the anticancer activity of ZnO-NPs is their semiconductor nature, which induces oxidative stress in cancer cells by generation of ROS and therefore leads to the death of cancer cells [ 69 , 70 , 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, chloroquine highly inhibited HCoV-229E replication in epithelial lung cell cultures 76 . It became apparent that the Zika virus provided a regional threat for Latin America and the Caribbean 77 , 78 .
Figure 6 Inhibition of dengue virus (DEN-2) post-treatment with 4,7-dichloroquinoline.
…”
Section: Resultsmentioning
confidence: 99%